PENGARUH SENAM AEROBIK TERHADAP KEBUGARAN FlSIK PEGAWAI RSUD DR. SOETOMO SURABAYA - Tumini .; Hanang Soejoedi; Adin Mu'afiro; Kiaonarni OW (JURNAL PENELITIAN KESEHATAN, 2015)
Aerobics is an exercise that uses all the musdes; especially the muscles - big muscles, it continues continuous,rhythmic, advanced and sustainable. Objective To analyze the effect of the research isaerobics on physical fitness of employees in Hospital Dr Soetomo. The method used is quasy Experimentpre-test - post-test one group. Thestudy population was all employees who follow aerobics as many as 80people. The research sample of some employees who follow aerobics taken using simple random samplingwith the lottery. Research variables are independent variables: Aerobic Gymnasticsand physical fitness ofemployees dependent variable. ResearchInstrument: observation sheet. Data analysis WIth the Wilcoxonstatistical test. The results showed aerobics for 4 weeks influence the change of physical fitness ofemployees (V02 max value). Employees who follow aerobics in Hospital Dr Soetomo V02 max valuesobtained approximately by 5 people (25%), for pretty much the value of V02 max 7 people (35%), goodfor V02 max value of 8mothers (40%). It is recommended to employees to do aerobics and fitness teston a regular basisKey words: aerobics, titness, employee